1991
DOI: 10.1118/1.596719
|View full text |Cite
|
Sign up to set email alerts
|

Energy constancy checking for electron beams using a wedge‐shaped solid phantom combined with a beam profile scanner

Abstract: An energy constancy checking method is presented which involves a specially designed wedge-shaped solid phantom in combination with a multiple channel ionization chamber array known as the Thebes device. Once the phantom/beam scanner combination is set up, measurements for all electron energies can be made and evaluated without re-entering the treatment room. This is also valid for the readjustment of beam energies which are found to deviate from required settings. The immediate presentation of the measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Rosenow et al used one‐dimensional (1D) ionization chamber array combined with a simple wedge‐shaped polystyrene phantom to measure beam energies. They found that the full width at half maximum (FWHM) of the modified electron profiles correlated linearly with R 50 in the whole range of energies studied . Using the same 1D ionization chamber array and similar wedge‐shaped polystyrene phantom, Islam et al were able to reproduce depth ionization curves in polystyrene phantom and the results agree quite well within water measurements for beam energy ≤10 MeV.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Rosenow et al used one‐dimensional (1D) ionization chamber array combined with a simple wedge‐shaped polystyrene phantom to measure beam energies. They found that the full width at half maximum (FWHM) of the modified electron profiles correlated linearly with R 50 in the whole range of energies studied . Using the same 1D ionization chamber array and similar wedge‐shaped polystyrene phantom, Islam et al were able to reproduce depth ionization curves in polystyrene phantom and the results agree quite well within water measurements for beam energy ≤10 MeV.…”
Section: Introductionmentioning
confidence: 82%
“…Measuring changes in R 50 with an ionization chamber array combined with a double‐wedge gives equivalent result as in water scans without requiring the user to change depths between energies as well as providing the flatness and symmetry measurement simultaneously. Compared to other approaches using 1D/2D planner array, the method examined in this work has advantages: (a) the setup is easy and the baseline calibration is straightforward; (b) the Profiler software can directly report the value of R 50 ; (c) the flatness and symmetry in principal axes and the beam energy R 50 can be measured in one profile acquisition. We have also demonstrated that a modification of the calibration procedure to include the off‐axis corrections in the calibration would allow this ICA/DWP to directly determine R 50 on different beams/machine types universally.…”
Section: Discussionmentioning
confidence: 99%
“…However, one needs to bear in mind that, while exact determination of R50 is required for dosimetry protocols such as TG‐51, the beam quality index for monthly QA is merely a constancy test that does not require exact determination of normalR50. Different methods have been proposed to determine energy constancy for QA checks 8 , 9 , 10 , 11 , 12 , 13 , 14 . A common method is to take the ratio of ion chamber measurements at two depths.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements taken from the profile underneath the wedge can be correlated with the beam energy. (5)(6)(7) Wells et al (8) introduced a double wedge technique for measuring electron beam energy that is invariant to phantom alignment in the wedge direction, and had a similar sensitivity to water tank measurements for electron energies between 6 and 20 MeV. They used a phantom with two PMMA wedges attached to a diode array to produce profiles at a fixed source-to-surface distance (SSD) and field size.…”
Section: Introductionmentioning
confidence: 99%